Soil microbial structure and activity in a semiarid rangeland of Patagonia, Argentina: Plant species and defoliation effects - Ambrosino, Mariela Lis (2021)
Natural grasslands are an important renewable resource for livestock production. Grazing in these areas alters the plant community composition, litter quality, and soil microbial structure and activity. Three cool-season species were studied in a semiarid rangeland area of Argentina: Poa ligularis and Nassella tenuis (desirable/ preferred for livestock) and Amelichloa ambigua (undesirable/non preferred). The objective was to analyze the effect of moderate defoliation and plant species on the structure and activity of soil microbial communities associated with their roots. In winter 2012, soil samples (0–10 cm) were taken underneath marked plant canopies of the three species (n = 8). Immediately thereafter, half of the plants (n = 4) were defoliated (5 cm stubble height) and the other half remained undefoliated (controls). The defoliation treatment was conducted again in the spring. Soil samples were taken 30 days after each defoliation event. The study was repeated in 2013, using a different plant set. Bacterial community structure and soil microbial activity were analyzed using PCR-DGGE analysis and basal soil respiration, respectively. Moderate and early defoliations allowed compensatory growth in the defoliated plants. Variations in the soil genetic profiles of A. ambigua suggest a higher dependence on its rhizospheric bacterial communities. Defoliation treatments did not substantially affect basal soil respiration but showed strong links between desirable species and soil microbial activity. Sustainable management practices that promote the persistence of these species are important for the development of microbial communities that respond quickly to stress conditions, favoring decomposition processes that maintain soil fertility in semiarid grasslands.